Ultrasonic-Assisted Extraction of Raspberry Seed Oil and Evaluation of Its Physicochemical Properties, Fatty Acid Compositions and Antioxidant Activities - Teng, Hui; Chen, Lei; Huang, Qun; Wang, Jinli; Lin, Qiyang; Liu, Mingxin; Lee, Won Young; Song, Hongbo (PLOS ONE, 2016)
Ultrasonic-assisted extraction was employed for highly efficient separation of aroma oil from raspberry seeds. A central composite design with two variables and five levels was employed and effects of process variables of sonication time and extraction temperature on oil recovery and quality were investigated. Optimal conditions predicted by response surface methodology were sonication time of 37 min and extraction temperature of 54°C. Specifically, ultrasonic-assisted extraction (UAE) was able to provide a higher content of beneficial unsaturated fatty acids, whereas conventional Soxhlet extraction (SE) resulted in a higher amount of saturated fatty acids. Moreover, raspberry seed oil contained abundant amounts of edible linoleic acid and linolenic acid, which suggest raspberry seeds could be valuable edible sources of natural γ-linolenic acid products. In comparison with SE, UAE exerted higher free radical scavenging capacities. In addition, UAE significantly blocked H2O2-induced intracellular reactive oxygen species (ROS) generation.